Sistem Pendukung Keputusan Reward Penyidik Terbaik Berbasis Web Menggunakan AHP-SAW - Ivone Djafar; Hilmansyah Gani; Alter Lasarudin; Wahyudin Hasyim (Prodi Teknik Informatika Universitas Pasir Pengaraian, 2026)
The investigator reward process at the Narcotics Investigation Directorate of Gorontalo Regional Police is still conducted manually, making it prone to subjectivity, inconsistency, and time-consuming evaluations. This study aims to develop a web-based Decision Support System (DSS) for selecting the best investigator using the Analytical Hierarchy Process (AHP) and Simple Additive Weighting (SAW) methods. The system was developed using the Rapid Application Development (RAD) approach and evaluated 20 investigator alternatives based on five criteria: Electronic Management of Investigators (EMP), Case Resolution, Discipline, Integrity, and Teamwork. The AHP method was applied to determine the priority weights of the evaluation criteria, while the SAW method was used to calculate preference values and rank the alternatives. The results show that Electronic Management of Investigators (EMP) is the most influential criterion with a weight of 41.62%, while alternative A2 achieved the highest preference value of 0.8923, making it the recommended best investigator. The developed system successfully automates the weighting, ranking, and reporting processes, thereby supporting a more objective, transparent, and measurable decision-making process. The novelty of this study lies in the development of a web-based DSS that integrates administrative and behavioral performance indicators into a single evaluation model for investigator reward selection, providing a more comprehensive assessment than conventional evaluation approaches.